Impact of antibiotic treatment for chronic endometritis on pregnancy outcomes in women with reproductive failures (RIF and RPL): A systematic review and meta-analysis - Liu, Jingjing; Liu, Zheng Ai; Liu, Yichun; Cheng, Lei; Yan, Lei (Frontiers in Medicine, 2022)
Objective The aim of this study was to investigate the effect of antibiotic treatment for chronic endometritis (CE) on reproductive outcomes. Design Systematic review and meta-analysis. Patients Women with reproductive failures, including recurrent implantation failure (RIF), and recurrent pregnancy loss (RPL). Interventions Literature searches were performed using three electronic databases (PubMed, Embase, and Web of Science) until 1 December 2021 (without date restriction). The following comparators were included: women with CE receiving antibiotics vs. untreated controls; women with cured CE vs. women with normal endometrial histology (negative for CE); and women with cured CE vs. women with persistent CE (PCE). The summary measures were indicated as odds ratio (OR) with a 95% confidence interval (CI). Main outcome measures These include on-going pregnancy rate/live birth rate (OPR/LBR), clinical pregnancy rate (CPR), and miscarriage rate/pregnancy loss rate (MR/PLR). Results A total of 2,154 women (from twelve studies) were enrolled. Compared with the control group, women with CE receiving antibiotics did not show a statistically significant difference in OPR/LBR (P = 0.09) and CPR (P = 0.36), although there was a lower MR (P = 0.03). Women with cured CE have higher OPR/LBR (OR 1.57) and CPR (OR 1.56) in comparison with those with non-CE. There was a statistically significantly higher OPR/LBR (OR 6.82, P < 0.00001) and CPR (OR 9.75, P < 0.00001) in women with cured CE vs. those with persistent CE. Conclusion While antibiotic treatment is a sensible option to cure CE, more well-designed prospective studies are needed to evaluate the reproductive impact of antibiotic treatment. Cured CE provides high-quality maternal conditions for subsequent embryo transfer and successful pregnancy.